Implementation of Administrative Sanctions Against Violations of Health Protocol Covid-19 in Central Lampung - Patar Daniel Panggabean (Administrative and Environmental Law Review, 2022)
In 2019, the world was hit by a pandemic that changed all the habits of the world's people. The pandemic was caused by the emergence of a virus that could threaten a person's life and many died due to the virus, namely Covid-19. The Indonesian government, both central and regional, has created a policy to limit the spread of the virus. But, of course, the implementation does not always match what has been expected. Therefore, on this occasion, the author wants to research how to implement administrative sanctions for violations of the Covid-19 health protocol by people in Central Lampung. This research uses normative juridical research methods and is also assisted by empirical legal research in Central Lampung Regency. In general, research activities are carried out by collecting sources from reading materials such as books, laws and regulations as well as conducting several interviews. The results from this study show that the Covid-19 health protocol in Central Lampung has been carried out appropriately by law enforcement and the community. In this case, the Central Lampung Regency Government has carried out its duties well and followed the instructions set by the President, namely Presidential Instruction No. 6 of 2020. At the regional level, the regional government has also made a policy, one of which is Regional Regulation No. 10 of 2020. Implementing administrative law against health protocol violations has also been maximally carried out in Central Lampung Regency. Law enforcers give verbal warnings first before giving other administrative sanctions, such as fines if they continue to violate. Then business actors are given administrative sanctions in the form of fines for revocation of permits. Still, in this case, the punishment for revocation permits is rarely carried out.